The Quest for Truth and Identity in Thomas Pynchon’s The Crying of Lot 49 - Abdelalim , Mohammed Taha; Halimi ,Mohammed Seghir (Faculty of Letters and Foreign Languages Department of English, 2018)
The two concepts of truth and identity have been a major subject for debate among critics and writers. This research seeks to explore the two concepts in postmodern thinking through the novel of Thomas Pynchon: The Crying of Lot 49. The two concepts are discussed through the quest of Oedipa, the protagonist of Pynchon’s novel, and her journey to execute her friend’s will. In addition, this study focuses on the absence of meaning in Oedipa’s world and her inability of making sense of it. Her mission is made harder by the obstacles that she faces along the way; this hinders the process of acquiring the truth and executing the will. Eventually, Oedipa seems to be suffering from identity problems. This study reveals that the uncertainty and absence of truth around Oedipa contribute to her disillusionment about her life; everything she encountered during her quest for meaning seemed to more confusing that revealing. This research points out relationship between the prevalence of uncertainty and Oedipa’s identity disorders. It argues that Oedipa’s incapability of making sense of the world causes her sufferance with distinguishing between reality and fiction. Eventually, Oedipa’s puzzlement leads to paranoia and schizophrenia where she doubts that she is a victim of a conspiracy